Solar energy harnessing in hexagonally arranged Si nanowire arrays and effects of array symmetry on optical characteristics - Li, Junshuai (2013)
Investigation of solar energy harvesting in hexagonally arranged Si nanowire (NW) arrays is performed through optimizing the structural parameters, such as array periodicity (P), Si NW diameter (D) and length (L). The results demonstrate that there exist wide P and D/P 'windows' for the Si NW arrays, locating around 600 nm and 0.833 (i.e., D = 500 nm), respectively, for achieving enhanced light absorption compared to their thin film counterparts with the same thickness, but with much less materials consumption. Calculation of the ultimate efficiency (UE) indicates that the light trapping capability is not monotonically increased with L, and that UE vibration is found when L is >1000 nm. Comparison of the light absorption spectra for hexagonally and squarely arranged Si NW arrays demonstrates that these two most widely employed array symmetries in practice have little impact on the light trapping capability.